The administration of the disability grant by the South African Social Security Agency within Makhuduthamaga Local Municipality, Limpopo Province - Sekele, Mantima Anna (My University, 2017)
The disability grant administration and dispensation has always been a challenge to the Department of Social Development and cause for concern from recipients of the disability grant. The Government decided on establishing the South African Social Security Agency (SASSA) as an entity to specifically deal with the administration of social grants including the Disability Grant. A number of studies have been conducted around the management and administration of the disability grant. The purpose of this study was to assess the efficiency and effectiveness of the administration and management of the disability grant. It further shows that the South African government spends a substantial amount of money in dispensing this grant. It is therefore necessary to investigate through an empirical research if these funds reach their intended beneficiaries, namely, the disabled community. This study employed the qualitative method which involved documents analysis, Questionnaire, interview and observation. Policy documents and reports from SASSA were analysed. Twenty applicants and twelve officials and three assessing doctors were interviewed. The findings of the study reveal that, although the SASSA has an improved model in place to redress and to contribute towards the effectiveness of the administration, there are still certain policy areas that needs to be reviewed. These policy areas include, amongst others, the appeal process, turnaround time, access and processing of the grant. In view of the findings from this study, the major recommendation is that there is a need to review the current booking system to ensure that the applicants are not subjected to unnecessary transports costs, time and delays. The SASSA needs to embark on vigorous and on-going community campaigns to educate the society on the operations of the SASSA and its jurisdiction within the Makhuduthamaga area. KEYWORDS: Administration; applicants; assessment; beneficiaries; Care Dependency Grant; Disability Grant; Grant-in-Aid; Makhuduthamaga; Recipients and the SASSA.
Thesis (MPA.) -- University of Limpopo, 2017
Keywords: beneficiaries; Care Dependency Grant.; Disability Grant; Grant-in-Aid; Makhuduthamaga; Makhuduthamaga; Beneficiaries; Care Dependency Grant.; Social security - Law and legislation - South Africa.; Capacity and disability - South Africa; People with social disabilities - Bibliography